2017
DOI: 10.13189/ojdom.2017.050302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medications, Dietary Supplements and Psychosocial Interventions in Burning Mouth Syndrome Patients: A Systematic Review with Meta-analyses

Abstract: The objective of this review is to determine the efficacy of cognitive behavioral therapy, oral and topical medications as well as dietary supplements to reduce pain in burning mouth syndrome patients (BMS). Methods: The Cochrane Library, Medline via PubMed and Web of Science were searched. Eligible studies were limited to randomized placebo-controlled trials on interventions used to treat BMS. Risk of bias was independently assessed in triplicate. Results: Twenty-two studies were included in this review. Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(152 reference statements)
1
1
0
Order By: Relevance
“…The pooled results showed that patients receiving ALA were 92% more likely to have an improvement in BMS symptoms (P = 0.031). These results are consistent with reviews by De Souza et al [ 28 ], Liu et al [ 14 ], and Phan et al [ 29 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The pooled results showed that patients receiving ALA were 92% more likely to have an improvement in BMS symptoms (P = 0.031). These results are consistent with reviews by De Souza et al [ 28 ], Liu et al [ 14 ], and Phan et al [ 29 ].…”
Section: Discussionsupporting
confidence: 94%
“…Liu et al [ 14 ] reported that five of six studies showed an improvement, with no significant differences in pain scores between ALA and placebo. Phan et al [ 29 ] reported that ALA showed no significant difference in pain reduction from placebo (P = 0.713) and that ALA significantly improved patients’ symptoms in four studies (RR = 2.676; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%